Pengaruh Tingkat Kecemasan Matematika terhadap Hasil Tes Penalaran Matematis pada Siswa Kelas V SD 5 Mejobo - Salsa Bela Anggraini; Fatikhul Ummam; Melda Puspita Sari; Fitriyah Amaliyah (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research aims to determine the effect of mathematical anxiety on the results of mathematical reasoning tests. This is motivated by the emergence of anxiety experienced by students when learning mathematics which affects the results of students' mathematical reasoning tests. The research method used in this research is a quantitative research method with the aim of testing a predetermined hypothesis and the data analysis technique used is an inferential statistical analysis technique with a simple linear regression test. The population of this study were 18 fifth grade students at SD 5 Mejobo, consisting of 11 boys and 7 girls. The data used is secondary data in the form of student anxiety questionnaire data and data from mathematical reasoning results. Class V anxiety is in the average category, the calculation results are included in the anxiety category. Mathematics anxiety has a negative effect on the results of fifth grade students' mathematical reasoning tests and the effect is 70.9%.